On ancestry, my grandmother Eliza and the Russian Theatre - Liparotti, Thábata Marques (2020)
This panel is the result of a pursuit of a writing style to a research on Art. Entwining childhood and Ukrainian ancestral memories, the seam and the embroidery emerged as a qualitative strategy to deal with the body's thinking. Such memories organizedthus the way this body creates and builds its connections. Since the weave resumes doings apprehended in childhood, the thread enters the textile and ties the links among academic, artistic and pedagogical creation which here are such an amalgam. Consequentily, three dimensions of sewing and embroidering may bepointed out: the metaphorical seams which tied ideas into a text, the metaphorical weaving of dance movements and the concrete seam of the text-tissue which bindsthe texts among them. All seams, therefore, embroider overlapping meanings and produce aesthetic results.